Analysis of Teachers' Creativity in Designing and Managing Mathematics Learning in Primary School - Aristanto, Aristanto; Zahra, Siti Fatimahtun; Muflihah, Siti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
Creativity is an important competency that teachers must have to support effective learning. This study describes teachers' creativity in designing and managing mathematics learning in elementary school grades 1, 2, and 3. The research uses a descriptive qualitative method involving 3 teachers and 25 students. Data is collected through interviews, observations, and document analysis. The study results show that each teacher applies different creativity according to students' needs and character, positively affecting motivation and learning outcomes. Creativity can be seen in planning teaching materials, classroom management, and learning methods. The results of the midterm exam and motivation questionnaire showed a significant improvement. This research emphasizes the importance of discussion and collaboration between teachers to develop innovative ideas in mathematics learning. The practical implication is that schools need to support teacher training to increase creativity so learning is more interesting and effective in helping students understand the material.